Metformin Enhances Doxycycline Efficacy Against Pasteurella multocida: Evidence from In Vitro, In Vivo, and Morphological Studies - Jiang, Nansong; Wang, Weiwei; Liang, Qizhang; Fu, Qiuling; Liu, Rongchang; Fu, Guanghua; Wan, Chunhe; Cheng, Longfei; Huang, Yu; Chen, Hongmei (Microorganisms (Basel), 2025)
Pasteurella multocida (Pm) is a zoonotic pathogen that poses a significant threat to animal health and causes substantial economic losses, further aggravated by rising tetracycline resistance. To restore the efficacy of tetracyclines to Pm, we evaluated the synergistic antibacterial activity of doxycycline combined with metformin, an FDA-approved antidiabetic agent. Among several non-antibiotic adjuvant candidates, metformin exhibited the most potent in vitro synergy with doxycycline, especially against capsular serogroup A strain (PmA). The combination demonstrated minimal cytotoxicity and hemolysis in both mammalian and avian cells and effectively inhibited resistance development under doxycycline pressure. At 50 mg/kg each, the combination of metformin and doxycycline significantly reduced mortality in mice and ducks acutely infected with PmA (from 100% to 60%), decreased pulmonary bacterial burdens, and alleviated tissue inflammation and damage. Mechanistic validation confirmed that metformin enhances membrane permeability in Pm without compromising membrane integrity, dissipates membrane potential, increases intracellular doxycycline accumulation, and downregulates the transcription of the tetracycline efflux gene tet(B). Morphological analyses further revealed pronounced membrane deformation and possible leakage of intracellular contents. These findings highlight metformin as a potent, low-toxicity tetracycline adjuvant with cross-species efficacy, offering a promising therapeutic approach for managing tetracycline-resistant Pm infections.